2022
DOI: 10.3390/plants11030405
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Root Imaging Analysis Reveals Wide Variation in Root Morphology of Wild Adzuki bean (Vigna angularis) Accessions

Abstract: Root system architecture and morphological diversification in wild accessions are important for crop improvement and productivity in adzuki beans. In this study, via analysis using 2-dimensional (2D) root imaging and WinRHIZO Pro software, we described the root traits of 61 adzuki bean accessions in their early vegetative growth stage. These accessions were chosen for study because they are used in Korea’s crop improvement programs; however, their root traits have not been sufficiently investigated. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
8
8
0
Order By: Relevance
“…RMTs, can therefore serve a number of purposes, including seggregation of plants and prediction of yield, which can be very useful for breeding. Statistical analysis of our data using ANOVA indicated that our results showed a clear seggregation of germplasms compared to previous research conducted using the same methods [ 13 , 14 ]. In our study, all eight RMTs were found to be significantly different between the germplasms, and there was homogenecity among the three replications within each accession, whereas the previous study indicated two RMTs to be significantly variable across the studied germplasms ( Table 2 ) [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…RMTs, can therefore serve a number of purposes, including seggregation of plants and prediction of yield, which can be very useful for breeding. Statistical analysis of our data using ANOVA indicated that our results showed a clear seggregation of germplasms compared to previous research conducted using the same methods [ 13 , 14 ]. In our study, all eight RMTs were found to be significantly different between the germplasms, and there was homogenecity among the three replications within each accession, whereas the previous study indicated two RMTs to be significantly variable across the studied germplasms ( Table 2 ) [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 53%
“…Statistical analysis of our data using ANOVA indicated that our results showed a clear seggregation of germplasms compared to previous research conducted using the same methods [ 13 , 14 ]. In our study, all eight RMTs were found to be significantly different between the germplasms, and there was homogenecity among the three replications within each accession, whereas the previous study indicated two RMTs to be significantly variable across the studied germplasms ( Table 2 ) [ 13 , 14 ]. In the present experiment, soybeans were grown in fields for two consecutive years (2019–2020), heterogeneous germplasms within accessions were removed according to agronomic characteristics (UPOV guidelines), and resources with a high seed vitality, as well as uniformity, were used.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations